Biomarkers in tongue cancer: understanding the molecular basis and their clinical implications. Issue 1015 (14th April 2010) - Zheng, Min; Li, Li; Tang, Ya-ling; Liang, Xin-hua
Abstract : Tongue cancer, one of the most common malignant cancers of the oral cavity, still affects human health worldwide due to its disappointing survival rates, despite significant developments in its multimodality treatment. The predominant cause of death in patients with tongue cancer is the high occurrence of invasion to surrounding tissues, lymph and distant metastasis, and recurrence. Due to the limited value of conventional predictive and prognostic factors and the uniformity of treatment strategies, several patients are still over- or under-treated, with significantly personal and socioeconomic impact. This review focuses on some promising predictive and prognostic biomarkers of tongue cancer and their actual/potential clinical implications, in order to provide clinicians with useful information for the improvement of early diagnostic/prognostic evaluation and management of patients with tongue cancer.